Macroeconomic Determinants of Price Dynamics in the Indian Stock Market - Kumar, Neeraj; Goel, Deepika (Indian Journal of Finance, 2024)
Purpose : The objective of this study was to analyze a long-term relationship between Indian stock prices and selected macroeconomic indicators. This paper investigated the long-term determinants of Indian stock prices, using monthly data from April 2005 to April 2024. Methodology : The paper used Johansen’s cointegration and vector error correction technique to investigate the short-run dynamic linkages among Indian stock prices and key macroeconomic indicators. Further, a dynamic analysis of the determinants using impulse response function (IRF), forecast error variance decomposition (FEVD), and Granger causality was also conducted. Findings : The empirical results showed a significant long-term relationship (cointegration) between Indian stock market performance and macroeconomic indicators like the index of industrial production, inflation, money supply, interest rate, rupee-dollar exchange rate, net exports, and global financial market performance. The signs in the cointegrating vector were consistent with the theoretical understanding of the relationship among variables. The generalized variance decompositions suggested that the level of economic activity in the domestic economy, exchange rate movements, and the global financial environment were the most important determinants of the Indian stock market. Practical Implications : Stock markets were a crucial part of a financial economy and played a phenomenal role in the growth and development of a nation. Markets worldwide have become more open and integrated. Hence, an economy’s vulnerability to the global environment, including exogenous shocks and events, such as the 2008 global financial recession and the COVID-19 pandemic, had increased. It had become imperative to review the role of macroeconomic fundamentals in determining stock prices while accounting for such random events. The Indian stock market was sensitive to both domestic and global factors. Hence, targeting exchange rates and capital flows as policy variables was equally important as domestic fundamentals, such as economic activity. Originality : This study included domestic and global factors as determinants of stock market prices. These findings had important policy implications as they might be crucial in the context of macroeconomic stabilization and adjustment programs.